Emergency clinicians' knowledge, preparedness and experiences of managing COVID-19 during the 2020 global pandemic in Australian healthcare settings. (September 2021) - Li, Cecilia; Sotomayor-Castillo, Cristina; Nahidi, Shizar; Kuznetsov, Sergey; Considine, Julie; Curtis, Kate; Fry, Margaret; Morgan, Dominic; Walker, Tony; Burgess, Alaine; Carver, Hamish; Doyle, Brian; et al.
Abstract: Background: Emergency clinicians have a crucial role during public health emergencies and have been at the frontline during the COVID-19 pandemic. This study examined the knowledge, preparedness and experiences of Australian emergency nurses, emergency physicians and paramedics in managing COVID-19. Methods: A voluntary cross-sectional study of members of the College of Emergency Nursing Australasia, the Australasian College for Emergency Medicine, and the Australasian College of Paramedicine was conducted using an online survey (June-September 2020). Results: Of the 159 emergency nurses, 110 emergency physicians and 161 paramedics, 67.3–78% from each group indicated that their current knowledge of COVID-19 was 'good to very good'. The most frequently accessed source of COVID-19 information was from state department of health websites. Most of the respondents in each group (77.6–86.4%) received COVID-19 specific training and education, including personal protective equipment (PPE) usage. One-third of paramedics reported that their workload 'had lessened' while 36.4–40% of emergency nurses and physicians stated that their workload had 'considerably increased'. Common concerns raised included disease transmission to family, public complacency, and PPE availability. Conclusions: Extensive training and education and adequate support helped prepare emergency clinicians to manage COVID-19 patients. Challenges included inconsistent and rapidly changing communications and availability of PPE.